ANALISIS PENGUKURAN KINERJA KEUANGAN KANTOR IMIGRASI TANJUNG BALAI ASAHAN BERDASARKAN KONSEP VALUE FOR MONEY - Rendiani Sitorus, Seftia; Siregar, Saparuddin (Jurnal Ekonomi STIEP, 2023)
To assess the responsibilities of the Tanjung Balai Asahan Immigration Office, measuring financial performance is crucial. The aim of this research is to evaluate the concept of value for money, especially economics, efficiency and effectiveness to find out how well the Tanjung Balai Asahan Immigration Office is performing. Evaluation of the Tanjung Balai Asahan Immigration Office uses a descriptive qualitative research method of case study analysis. By reviewing information on immigration developments at Tanjung Balai Asahan in 2019–2020, this research is descriptive in nature. The results of the study show that the performance of the Immigration Office: 1) economically with an average economic ratio below 100%; 2) effective with an average ratio of effectiveness below 100%; and 3) efficient with an average effectiveness ratio above 100%. Because it is so economical, efficient and successful, good governance at the immigration office can be achieved if it is evaluated based on calculations using the idea of value for money.